Performance Indicators Predicting Medallists and Non-medallists in Elite Men Volleyball Competition - Abdullah, Prof. Madya Dr. Mohamad Razali (Springer Science and Business Media Deutschland GmbH, 2021)
In this chapter, we investigated the influence of technical and tactical performance indicators in determining the match outcome, i.e. medallists and non-medallists during an indoor volleyball competition. A set of performance indicators, namely the ability to block, spike as well as tap, are shown to be essential in determining the chances of a team to either earn or lose a medal. It has been shown that both technical and tactical skills are essential for ensuring success in the men elite indoor volleyball championship. Moreover, a stacking-based machine learning approach was found to be effective in the identification of the chances for winning or losing a medal during a volleyball competition. © 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.